Aspects of health and the environment related to consumption of organic foods - Albuquerque Júnior, Edmilson Pinto de; Silva Filho, José Carlos Lázaro da; Costa, Josimar Souza; Santos, Sandra Maria dos (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346598812 Organic food is considered healthy and environmentally friendly, then becoming relevant the investigation about these two constructs associated to the purchase intention of consumers. This study sought to investigate which aspect, among those related to the environmental awareness and the pursuing of health, has greater influence on the shopping intentions of the consumer of organic fruits and vegetables (FV). To this end, it was applied a survey research type. The sample involved 200 interviewees. The questionnaires were applied from February to March, 2012, at two distribution channels of organic food in the city of Fortaleza, Ceará: agroecological fair and supermarkets. The factor analysis was employed for the statistical analysis of data by using the SPSS software, version 20. The results indicate that the aspects concerning health present more influence on the purchase intentions related to that type of food. From a managerial point of view, the contributions from this study reside in the comprehension of the determining variables of the purchase behavior of an ascending market, what suggests basis to the development of strategies, by the agents of the productive chain, adequate to the analyzed market.